Implementation Of Permen Esdm No. 17/2012 As A Solution Between Mineral Businessesand Conservation Karst Zone In Indonesia - Aris Dwi Nugroho; Tantan Hidayat; Muhammad Wachyudi Memed (Indonesian Mining Professionals Journal, 2019)
Cement is powder made from lime and other materials used to make concrete, glue bricks or make walls (KBBI, 2008). Cement is a material that is hydraulic in nature, that is, a material which will undergo a hardening process in its mixing with water or acid solution. The raw materials for making cement include: clinker / slag of cement as much as 70% - 95% (the results of the combustion of limestone, silica sand, iron sand and clay), 5% gypsum and other additional materials (limestone, pozzolan, fly ash and etc). Along with the increase in infrastructure development which is the focus of the Government at this time, the need for building materials, especially cement, has increased. This increase in demand has made cement companies increase production, which in turn will also reduce the limestone reserves that exist in nature. Geological resources consist of mineral resources, energy resources, water resources, and landscapes.  Limestone  as  one  of  the  dominant  raw  materials  for  making  cement  is  a  mineral  and landscape resource that must be protected. The Ministry of Energy and Natural Resources since 2012 has issued regulations relating to the use and protection of Karst Landscape Areas (Permen ESDM No. 17 of2012). Protection of the Karst Landscape Area aims to protect its function as a natural regulator of the water system and its unique / scientific value in the development of science. Meanwhile, the delineation of utilization efforts as minerals and industrial raw materials is regulated so that it does not disturb the conservation zone. Expected with the regulations (Permen  ESDM No. 17 of 2012) can be a solution for the use and protection of the Karst Landscape in Indonesia.